Pelatihan Desain Media Pembelajaran Worksheet Melalui Aplikasi Canva Bagi Guru - Ashoumi, Hilyah; Hariono, Tholib; Hidayatulloh, Muhammad Kris Yuan; Sirojudin, Didin (VINICHO MEDIA PUBLISINDO, 2023)
In this activity, training on making worksheet learning media using the Canva application was introduced to teachers of SDN Pacarpeluk, MI Miftahul Ulum and TK Pertiwi Pacarpeluk in Jombang, East Java. One application that can be used to help teachers in making teaching materials is Canva. The Canva application presents various features in making designs including worksheets. The KH. A. Wahab Hasbullah University community service team conducted training for Pacarpeluk Elementary School teachers on making worksheets with the Canva application. The approach method used in this service activity is the Community Based Research (CBR) approach with community involvement as partners who participate and are actively involved in all service activities. The results of this service activity are an increase in teacher creativity in making Canva-based worksheet learning media and the learning process that is carried out is more fun and for students of SDN Pacarpeluk, MI Miftahul Ulum and Pertiwi Kindergarten by using Worksheet media to increase students' activeness and memory of English, Arabic and Mathematics subject matter.